DIGITAL TRANSFORMATION OF TOURISM: THE IMPACT OF ARTIFICIAL INTELLIGENCE AND SOCIAL MEDIA ON THE FORMATION OF TOURIST BEHAVIOR - NESTORISHEN, Ihor; KOSOVSKA, Karina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the processes of digital transformation in the tourism industry under the combined influence of artificial intelligence and social media, emphasizing their role in shaping contemporary tourist behavior. The study substantiates that the rapid development of digital technologies fundamentally changes approaches to destination management, tourism service delivery, and consumer decision-making. Artificial intelligence tools are analyzed as key drivers of personalization, automation, and predictive analytics in tourism, enabling more efficient management of tourist flows, improved service quality, and the creation of customized travel experiences based on individual preferences, budgets, and behavioral patterns. Particular attention is paid to the role of social media as a dominant information environment that influences tourist perceptions, destination choice, and demand dynamics. User-generated content, influencer marketing, visual storytelling, and algorithm-driven content distribution significantly affect travel motivation, stimulate interest in specific destinations, and contribute to the rapid spread of tourism trends. The article highlights generational differences in platform usage and their implications for tourism marketing strategies. The research also identifies both positive and negative consequences of the growing reliance on digital platforms. While artificial intelligence and social media enhance accessibility, engagement, and operational efficiency, they simultaneously generate new challenges, including reputational risks, data privacy concerns, information distortion, and the risk of overtourism in popular destinations. The study emphasizes the importance of balancing technological innovation with ethical data use, cybersecurity, and sustainable tourism principles. Based on a PEST analysis, the article demonstrates that artificial intelligence primarily transforms operational and analytical processes, whereas social media reshapes the informational and behavioral landscape of tourism consumption. The findings confirm that the competitiveness of tourism enterprises increasingly depends on their ability to integrate digital technologies into strategic management, marketing communications, and service design. The article concludes that future development of the tourism sector requires adaptive digital strategies focused on sustainable growth, responsible innovation, and the preservation of the human-centered nature of travel experiences.